A Field Study on the Determination of the Credit Card Users’ Awareness Of the Products/Services Offered with Credit Cards: Turkey Case - Kizgin, Yildiray; Kizgin, Yildiray; Karaosmanoglu, Kubra; Kizgin, Yildiray; Hiz, Gulay; Karaosmanoglu, Kubra; Karaosmanoglu, Kubra; Benli, Tahir; Hiz, Gulay; Hiz, Gulay (Canadian Center of Science and Education, 2013)
One of the most powerful tools in helping businesses so as to gain a competitive edge is to produce innovative products. In order to emphasize the importance of innovation, the credit cards market has been selected in this article. The innovative products and services offered to credit card users by the banks have been investigated and discussed in an academic debate in this field. A questionnaire applied to 402 persons as to determine the credit card consumers’ use levels and awareness of credit card use in Turkey, and of an innovative product/service applications along with the credit cards.
Keywords: 9. Industry and infrastructure